Beyond the Ḥaram: Ibn al-Khaṭīb and His Privileged Knowledge of Royal Nasrid Women - Boloix-Gallardo, Bárbara (Medieval encounters, 2014)
One of the most difficult tasks of specialists devoted to the study of medieval Islamic societies is to reconstruct the historical role of women. The patriarchal interpretation of Islamic scriptural sources by largely male Muslim chroniclers, as well as the masculine nature of Arabic historiography, produced by and for men, determined the relegation of women to the background in both history and society. As a consequence, the presence of women was usually veiled in the chronicles, due to the exacerbated respect towards their identities stipulated by Muslim sacred texts, which recommended preserving women within the private area of society. However, some authors went beyond these conventions and offered interesting data concerning the women of the dynasty that they served. This was the case of Ibn al-Khaṭīb, whose work is unique and fundamental to our knowledge of the female sultans of the Alhambra and the particularities of the Nasrid harem, as we will prove throughout this paper.